Understand the Cultural Influence of Short Videos in the Communication of Public Health Information - Ren Changning; Akmar Hayati Ahmad Ghazali; Syafila Kamarudin (Jurnal the Messenger, 2025)
Introduction: Groups with different ideologies have different perspectives on civilization and, therefore, can exhibit various cultural values. In today's globalized world, people from different cultural backgrounds interact through the web, and using emerging communication technologies, such as short videos, is a challenge, especially in public health. Although studies have shown that globalization can alter the process of cultural production and consumption and strengthen cultural identity, there are still differences in cultural production and cultural identity in public health.